Knotted bull Diagnosis Treatment methods (Comment) (Texas Journal of Medical Science, 2022)
In this article analyzed the scientific literature of the last years on the nodal formations of thyroid glands. It highlights the methods of diagnosis and treatment of nodular goiter.